The world religions paradigm: Why context matters in religious studies - Vencatsamy, Beverly (Critical research on religion, 2024)
The World Religions Paradigm (WRP) has long served as the predominant framework for teaching Religious Studies globally and in South Africa. However, criticisms of the WRP highlight its tendency to marginalize non-Christian, non-Western, and non-white perspectives. This article examines these critiques in the context of South Africa, particularly in light of the events of 2015–2016, when the #MustFall movement sought to raise and address issues of decolonization. This article will argue that South Africa provides a pertinent example of the need to re-evaluate pedagogical choices in Religious Studies education by emphasizing the importance of context in re-shaping the curriculum.